Gerakan Sosial Politik Pesantren Takeran Magetan Di Era Jepang Sampai Kemerdekaan - Restu Damara, Adhie Handika (Kodifikasia, 2025)
The social movement of the Takeran Islamic boarding school in this article includes educational and political movements. Where the collective power of the movement built by the Islamic boarding school plays an important role in bringing about change in society. The restructuring of Islamic boarding school education and the political movement of the kiai in the Japanese era until independence had an impact on significant social transformation in society. The purpose of this article is to see the impact of the social movement of the Islamic boarding school. This research is a qualitative research, based on social history using a historical approach, with a time division from the Japanese occupation to independence. To describe this research, a systematic research method is needed with the heuristic method, data verification and data interpretation. The findings of this study show that the Takeran Islamic boarding school forms society into educated people and fosters a spirit of nationalism.